DLSU intranet is already on-line - De La Salle University, Manila (Animo Repository, 1998)
The Information Systems and Technology Center (ISTC) announced that the DLSU Intranet was already on-line. The Intranet can be accessed through any network-connected computer within the campus by clicking on The DLSU Intranet in the DLSU Web Page or typing in the URL (i.e., http://intranet.dlsu.edu.ph).